Determinants Influencing Malaysian University Students’ Continuance Intention to Adopt E-learning: A Structural Equation Modelling Approach - Chan, Shiau Wei; Wu, Longkai; Alice Lee Ke Jia,; Shafie Mohamed Zabri,; Fadillah Ismail, (Journal of Technical Education and Training, 2025)
E-learning, powered by technology and the internet, has become a dominant mode of education in today’s world. However, several factors influence students' continuance intention to adopt e-learning, including internet connectivity issues, low attendance rates, and inadequate instructor support. This study investigates the impact of these factors on university students' continuance intention to adopt e-learning, exploring the relationships between each determinant. A survey was administered to 210 undergraduate students at the Faculty of Technology Management and Business, Universiti Tun Hussein Onn Malaysia (UTHM), yielding 157 responses. Descriptive analysis and Partial Least Square Structural Equation Modeling (PLS-SEM) were used to analyze the data. The results revealed a strong influence of these factors on students' continuance intention to adopt e-learning. Specifically, perceived ease of use was positively correlated with perceived usefulness and continuance intention, while perceived enjoyment significantly affected perceived ease of use, perceived usefulness, and continuance intention. Perceived usefulness had a significant impact on continuance intention, and social influence also demonstrated a significant impact on continuance intention.  This study contributes to the understanding of factors influencing e-learning adoption and provides an extended model that incorporates motivational elements, offering valuable insights for future research and practical recommendations for enhancing e-learning experiences.